Religiosidade indígena e Diretório Pombalino - Oliveira, Giselly Silva de; Pereira, José Edson da silva; Soares, Maria Gisllainy Ribeiro; Cecília, Silvaneide (Anais dos Simpósios da ABHR, 2016)
Religiosidade indígena e Diretório Pombalino